Optimalisasi Rangkaian Alat Bongkar, Alat Muat Dan Alat Angkut Pada Penambangan Batugamping Di Quarry Sawangan PT Sinar Tambang Arthalestari (Semen Bima) - Mohd Prieska Hasela Ariki; Mulkal Mulkal; Febi Mutia (Journal of Geosciences, Mining Engineering, and Technology, 2022)
PT Sinar Tambang Arthalestari as the owner and producer of Semen Bima entrust PT Bintang Mitra Sejahtera to do mining services at Sawangan Limestone Quarry. Limestone is the main raw material for cement production. Limestone mining is done by using a series of heavy eqipments such as 3 units rock breaker, 3 units excavator and 9 units dump truck. The average daily production amounts to 4,989.59 tons of limestone, while daily production target is about 8,876 tons. Optimization methods are applied to obtain the target of daily production. Optimization  for breaking machine can be achieved by using 3 units of rock breaker with an efficiency of 51% worked for 12 hours and combined with 3 units of Surface Miner SM2200 worked for 8 hours. Meanwhile optimization for loader is adjusted by combining 2 units of Hitachi Zaxis 330 with an efficiency of 39% and 2 units of Doosan 340 LCV with an efficiency of 48%. The optimization of hauler is achieved by applying 15 units of dump truck with an efficiency of 51% that can be transported as much as 25 tonne of limestone per cycle to achieve the target of daily production. So in other words at least they need 4 fleets to achieve the target of daily production. The results of limestone production by using breaking machine and 4 fleet are respectively 11,841.03 tons and 10,182.8 tons.Keywords: rock breaker, surface miner, excavator, dump truck, road width, grade mining road, optimalization.